Pengaruh Kemampuan Kerja Terhadap Kinerja Pegawai Sekretariat DPRD Kota Banjar - Syara Agita; Rizka Nurlela; Suryadi Suryadi; Rahma Aulia Kharisma; Arie Buriawan; Dini Yuliani (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The performance of employees at the Banjar City DPRD Secretariat is suboptimal, while the formulation of the problem is how the influence of work ability on the performance of employees of the Banjar City DPRD Secretariat. The purpose of this study was to determine the effect of work ability on the performance of employees of the Banjar City DPRD Secretariat. This research uses Robins' (2012) theory of employability. This research method uses descriptive qualitative which is a research method that intends to describe all activities to solve problems, analyze social events that are being studied by researchers, carried out by direct observation to find information, collect and compile data systematically, then analyzed to solve a problem raised. The data collection techniques used are field studies through observation, interviews, and documentation. And literature study through the results of similar research that has been done, books, and journals related to this research. Based on the results of the study, it is known that the effect of work ability on the performance of employees of the Banjar City DPRD Secretariat such as not optimizing some employees in completing tasks and functions and frequent errors in administration caused by not being careful in working and miscommunication in delegating work.